Composite powder used for manufacturing of porous bodies contained in an anode body of electrolytic capacitor, manufacturing method of the composite powder, and manufacturing method of anode body for electrolytic capacitor
By using a composite powder with an alcohol compound attached to valve metal particles in the anode body of electrolytic capacitors, the method addresses high carbon content and mass variation, resulting in improved stability and reduced leakage current, thus enhancing capacitor quality.
Patent Information
- Application Number
- JP2023111406
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-20
AI Technical Summary
Existing methods for manufacturing electrolytic capacitors result in high carbon content from additives, leading to mass variation and increased leakage current, which affects the consistency and quality of the capacitors.
A composite powder is used for manufacturing the anode body of electrolytic capacitors, comprising a valve metal powder with an alcohol compound having a melting point of 35°C or higher attached to the surface of the particles, which is then processed to reduce carbon content and improve weighing stability.
The method reduces carbon content and mass variation, leading to improved weighing stability and reduced leakage current, enhancing the consistency and quality of the electrolytic capacitors.
Smart Images

Figure 2025008845000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composite powder used to manufacture a porous body contained in an anode body of an electrolytic capacitor, a method for manufacturing the composite powder, and a method for manufacturing an anode body for an electrolytic capacitor. [Background technology]
[0002] In recent years, electrolytic capacitors with small equivalent series resistance (ESR) and excellent frequency characteristics have been developed. The anode body of the electrolytic capacitor includes, for example, a porous body containing a valve metal and a dielectric layer covering the porous body. The raw material for the porous body is, for example, raw material powder containing a valve metal to which an additive (binder) is added.
[0003] Patent Document 1 proposes a "solid electrolytic capacitor including a capacitor element including a sintered porous anode body; a dielectric disposed on the anode body; and a solid electrolyte disposed on the dielectric body, the solid electrolyte including a conductive polymer and a depolarizer." Patent Document 1 also lists a powder containing tantalum as an example of a powder used to form the sintered porous anode body. An acrylic polymer is listed as an example of a binder used to aggregate the powder particles.
[0004] In Patent Document 2, "a tantalum powder containing tantalum, hydrogen doped in the tantalum, and nitrogen doped in the tantalum is described, and the hydrogen (H) content (ppm) of the tantalum powder is calculated based on the Brunauer-Emmett-Teller (BET) surface area (m 2 The tantalum powder has a hydrogen content of 300 ppm to 1200 ppm, a nitrogen content of 500 ppm to 3,500 ppm, and a hydrogen content of 300 ppm to 1,200 ppm. 2 / g~about 10m 2 / g」。 Furthermore, Patent Document 2 lists camphor as an example of a binder to be added to the tantalum powder.
[0005] Patent Document 3 proposes "a method for making an anode for an electrolytic capacitor, the method comprising the steps of combining a metal powder and an effective amount of dimethyl sulfone as a binder; pressing the powder and dimethyl sulfone to form an anode body; and removing the dimethyl sulfone." [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2022-533161 [Patent Document 2] Special Publication No. 2020-500260 [Patent Document 3] Special Publication No. 2003-509583 Summary of the Invention [Problem to be solved by the invention]
[0007] There is a demand for a porous body contained in an anode body of an electrolytic capacitor to have a reduced carbon content derived from additives that are added to raw material powder containing a valve metal during the porous body production process, and to have a reduced mass variation. [Means for solving the problem]
[0008] One aspect of the present disclosure relates to a composite powder used for manufacturing a porous body included in an anode body of an electrolytic capacitor, the composite powder including a raw material powder including a valve action metal and an alcohol compound (excluding a polymer) adhered to surfaces of particles of the raw material powder, and the alcohol compound has a melting point of 35°C or higher.
[0009] Another aspect of the present disclosure relates to a method for producing a composite powder used in producing a porous body included in an anode body of an electrolytic capacitor, the method including the steps of: preparing a raw material powder containing a valve action metal; preparing an alcohol solution containing an alcohol compound (excluding a polymer) having a melting point of 35°C or higher and a solvent; adding the alcohol solution to the raw material powder while stirring the raw material powder to obtain a wet raw material powder; and removing the solvent by drying the wet raw material powder while stirring to obtain a composite powder.
[0010] Yet another aspect of the present disclosure relates to a method for producing an anode body for an electrolytic capacitor, the method including the steps of: preparing a composite powder including a raw material powder including a valve action metal and an alcohol compound (excluding a polymer) adhered to surfaces of particles of the raw material powder; filling a predetermined molding die with the composite powder and pressure-molding the composite powder to obtain a molded body; removing the alcohol compound contained in the molded body; sintering the molded body from which the additive has been removed to obtain a porous body; and forming a dielectric layer on a surface of the porous body to obtain an anode body, wherein the melting point of the alcohol compound is 35° C. or higher. Effect of the Invention
[0011] According to the present disclosure, for a porous body included in an anode body of an electrolytic capacitor, it is possible to reduce the carbon content derived from additives added to raw material powder containing a valve metal during the production process of the porous body, and to reduce mass variation. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a diagram showing an example of wet mixing of a raw material powder and an alcohol compound A. [Diagram 2] 2 is a diagram showing an example of a process for producing a compact A from a composite powder, in which (a) shows the state of the composite powder when it is weighed, (b) shows the state of the composite powder before compression molding, and (c) shows the state of the composite powder during compression molding. [Diagram 3]FIG. 2 is a configuration diagram showing an example of equipment used in a step of removing an alcohol compound A and a step of sintering a green body. [Figure 4] 1 is a cross-sectional view illustrating a schematic diagram of an electrolytic capacitor according to an embodiment of the present disclosure. [Diagram 5] FIG. 11 is a cross-sectional view showing a state in which a powder is filled in a jig set for evaluating weighing stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In the following, the embodiment of the present disclosure will be described by way of example, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and materials may be applied as long as the effects of the present disclosure are obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "numerical value A or more and numerical value B or less." In the following description, when a lower limit and an upper limit are exemplified for numerical values of specific physical properties or conditions, any of the exemplified lower limits and any of the exemplified upper limits can be arbitrarily combined as long as the lower limit is not equal to or greater than the upper limit. When multiple materials are exemplified, one of them may be selected and used alone, or two or more may be used in combination.
[0014] The anode body of the electrolytic capacitor includes a porous body (porous sintered body) containing a valve metal, and a dielectric layer covering the surface of the porous body. The present disclosure relates to a composite powder used to manufacture the porous body contained in the anode body of the electrolytic capacitor. The composite powder according to the embodiment of the present disclosure includes a raw material powder containing a valve metal, and an alcohol compound (excluding polymers) attached to the surface of the particles of the raw material powder. The melting point of the alcohol compound is 35°C or higher.
[0015] Hereinafter, the alcohol compound (excluding polymers) having a melting point of 35°C or higher is also referred to as "alcohol compound A". The raw material powder particles are also referred to as "raw material particles". The composite powder particles have raw material particles and alcohol compound A attached to the surfaces of the raw material particles. Hereinafter, the composite powder particles are also referred to as "composite particles".
[0016] In the composite powder in which alcohol compound A is added as an additive to the raw material powder, the weighing stability (fluidity) can be improved. This can reduce the mass variation of the compact or porous body (anode body). Furthermore, in the case of alcohol compound A, the weighing stability of the powder can be sufficiently improved by adding a small amount, the carbon content derived from the additive in the porous body can be reduced, and the increase in leakage current when the carbon content is high can be suppressed.
[0017] In addition, the high weighing stability of the powder means that when the powder is weighed by filling the weighing hole of the weighing jig with the powder using a leveling jig, the variation in the amount of the powder filled into the weighing hole is small. The powder is weighed, for example, by filling the powder 300 into the weighing hole 420a in FIG. 2(a).
[0018] If the mass variation of the porous bodies is large, the surface area of the porous bodies (anode bodies) will vary greatly, which may increase the variation in the capacitance of the electrolytic capacitor. In addition, in the above case, when multiple porous bodies are subjected to a chemical conversion treatment at the same chemical conversion voltage at the same time, the chemical conversion current will vary greatly between the porous bodies, which will increase the variation in the film quality of the chemical conversion film formed, and this may increase the variation in the LC of the electrolytic capacitor. In this way, the variation in the characteristics of the electrolytic capacitor may increase. One method for reducing the variation in the characteristics of the electrolytic capacitor is to remove those that are outside a predetermined mass range as defective products at the stage of obtaining the molded body, but in the above case, the molding defect rate increases, which is disadvantageous in terms of productivity.
[0019] (Raw material powder) The raw material powder contains a valve metal. Examples of the valve metal include aluminum (Al), titanium (Ti), tantalum (Ta), niobium (Nb), zirconium (Zr), and hafnium (Hf). The raw material particles may be particles of a valve metal, particles of an alloy containing a valve metal, or particles of a compound containing a valve metal. Only one type of particle may be used, or two or more types may be mixed together.
[0020] The average particle size of the raw material powder may be 100 μm or less, or may be 80 μm or less. In this case, the increase in density variation of the molded body due to uneven distribution of coarse particles in part of the molded body can be suppressed, and the flatness of the surface of the molded body can be improved, thereby reducing the dimensional variation of the molded body. In addition, since it is relatively difficult to make the average particle size 100 μm or more in powders with a CV value of 100 μFV / g (100 kCV) or more, there is also an advantage that the options when selecting raw material powders are expanded. The addition of alcohol compound A can improve the weighing stability of raw material powders with an average particle size of 100 μm or less. If camphor is added to raw material powders with an average particle size of 100 μm or less, the weighing stability of the powder may decrease.
[0021] In addition, from the viewpoint of suppressing the powder from floating up into the air, the average particle size of the raw material powder may be 10 μm or more. In this case, the powder loss due to the powder floating up into the air when transferring from one container to another can be suppressed, and the risk of workers inhaling the powder can be reduced. In addition, the small particle size can also suppress the scattering of particles from the gaps in the molded parts.
[0022] The average particle size referred to here is the median diameter (D50) in the volume particle size distribution determined by a laser diffraction type particle size distribution measuring device.
[0023] (Alcohol compound A) The alcohol compound A has a melting point of 35° C. or higher and is stable in a solid state at room temperature. Therefore, the composite powder can be obtained as a dry powder, and excellent weighing stability can be ensured. The melting point of the alcohol compound A may be 40° C. or higher, or 45° C. or higher.
[0024] From the viewpoint of productivity in the step of removing the alcohol compound A described later, the melting point of the alcohol compound A is preferably 120° C. or less, more preferably 100° C. or less, even more preferably 90° C. or less, and particularly preferably 80° C. or less. When the melting point of the alcohol compound A is within the above range, in the step of removing the alcohol compound A using the equipment of FIG. 3, the adhesion of the alcohol compound A to the inner wall of the pipe can be suppressed by maintaining the pipe from the removal furnace of the alcohol compound A to the recovery tank at about 120 to 150° C. In addition, there is no need to install a pipe with a heat-resistant structure or to add equipment for heating the pipe to 150° C. or more, which is advantageous in terms of cost.
[0025] The boiling point of the alcohol compound A is preferably 400° C. or lower. In the step of removing the alcohol compound A, the alcohol compound A can be removed by evaporation at a temperature of 400 to 500° C. This temperature range is almost the same as the temperature range for removing camphor by evaporation and the temperature range for removing acrylic resin by thermal decomposition and evaporation, and the equipment used when camphor or acrylic resin was used as an additive can be used as is.
[0026] The alcohol compound A does not contain a polymer. Examples of the polymer include polyvinyl alcohol, polyalkylene glycol (polyethylene glycol, etc.), cellulose, etc. If the additive is a polymer, the amount of the polymer added to the raw powder may increase to improve weighing stability, and the carbon content of the porous body may increase. When a composite powder is obtained using a polymer, the polymer is likely to form agglomerates (e.g., 300 μm or more) of particles that are tightly adhered to each other after the solvent removal process. The agglomerates are likely to cause problems such as increased variation in the filling of the powder into the weighing hole, localized dense parts being formed inside the molded body, and the formation of a sintered body with an irregular shape. Therefore, a separate process for removing the agglomerates is required, which leads to powder loss and is disadvantageous in terms of productivity. Generally, a polymer is decomposed by heating into multiple substances, and the decomposition products evaporate, and the polymer or its decomposition products react with oxygen by combustion to generate CO2, H2O, etc., and these evaporate to remove the polymer. In the polymer removal process under reduced pressure, oxygen is hardly present, so decomposition products that do not evaporate remain as they are, and the carbon content after sintering tends to be high. In particular, it is known that polyvinyl alcohol generates a large amount of acetaldehyde, which is considered to be carcinogenic, due to thermal decomposition under low oxygen partial pressure, and the material recovered in the recovery tank must be treated separately by burning it in the air.
[0027] The number of carbon atoms of the alcohol compound A is, for example, 6 or more. The alcohol compound A may be used alone or in combination of two or more. The alcohol compound A preferably includes at least one selected from the group consisting of a monohydric alcohol compound A and a dihydric alcohol compound A.
[0028] Examples of the monohydric alcohol compound A include 1-tetradecanol, 1-pentadecanol, 1-hexadecanol, 1-heptadecanol, 1-octadecanol, 1-nonadecanol, 1-icosanol, 1-docosanol, 1-tetracosanol, 1-hexacosanol, 1-octacosanol, 1-triacontanol, etc. Among them, 1-hexadecanol and 1-octadecanol are preferred, and 1-hexadecanol is more preferred, from the viewpoints of low toxicity, high solubility in solvents, easy availability, cost reduction, etc.
[0029] Examples of the dihydric alcohol compound A include 1,2-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 2,3-dimethyl-2,3-butanediol, 2,2-diethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,9-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,2-hexadecanediol, and 1,16-hexadecanediol. Among these, 1,6-hexanediol, 1,10-decanediol, and 2,5-dimethyl-2,5-hexanediol are preferred from the viewpoints of low toxicity, high solubility in solvents, low flammability, high chemical stability, ease of storage (no need to store in a cold place, etc.), ease of availability, and cost reduction.
[0030] The content of the alcohol compound A in the composite powder is preferably 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder. When the content of the alcohol compound A is 0.1 parts by mass or less, the carbon content of the porous body is sufficiently reduced, and the leakage current is sufficiently reduced. In addition, the strength of the molded body is sufficiently ensured. When the content of the alcohol compound A is 0.002 parts by mass or more, the weighing stability of the composite powder is easily improved. From the viewpoint of further reducing the carbon content of the porous body, the content of the alcohol compound A is more preferably 0.002 parts by mass or more and 0.05 parts by mass or less. In addition, from the viewpoint of further improving the weighing stability of the powder, the content of the alcohol compound A is more preferably 0.005 parts by mass or more and 0.1 parts by mass or less. The content of the alcohol compound A is particularly preferably 0.005 parts by mass or more and 0.05 parts by mass or less.
[0031] If the additive is acrylic resin, the carbon content of the porous body increases, which may increase leakage current. Although the detailed reason is unclear, it is assumed that this is because it is necessary to add a large amount of acrylic resin (for example, add 1 part by mass or more of acrylic resin to 100 parts by mass of raw material powder) to improve weighing stability, and it is difficult to remove the pyrolysis products caused by pyrolysis in the additive removal process.
[0032] The content of additive (alcohol compound) in the composite powder (amount per 100 parts by mass of raw material powder) can be determined as follows. The composite powder is placed in an organic solvent such as ethanol, stirred, and then the raw material powder (e.g., Ta powder) and liquid (alcohol solution) are separated by filtration or centrifugation. The liquid is dried to obtain a precipitate (additive). The masses of the raw material powder and the precipitate are measured, and the ratio (percentage) of the mass of the precipitate to the mass of the raw material powder is determined.
[0033] The components of the additives can be determined, for example, by gas chromatography mass spectrometry. The melting point and boiling point are measured by a general method described, for example, in the Japanese Industrial Standards (JIS). If necessary, the melting point may be measured by differential scanning calorimetry (DSC). If necessary, the boiling point may be measured by thermogravimetry / differential thermal analysis (TG / DTA).
[0034] [Method of manufacturing composite powder] A manufacturing method for a composite powder according to an embodiment of the present disclosure includes a step of preparing a raw material powder containing a valve action metal, a step of preparing a solution of an alcohol compound A (hereinafter also referred to as "alcohol solution A"), a step of mixing the raw material powder with the alcohol solution A, and a step of removing the solvent.
[0035] When adding a small amount (for example, 0.1 parts by mass or less) of alcohol compound A to 100 parts by mass of raw powder, the alcohol compound A is dissolved in a solvent and mixed with the raw powder to produce a wet raw powder (wet mixing), which can produce a homogeneous composite powder. If a small amount of alcohol compound A is dry mixed with the raw powder at a temperature above the melting point of alcohol compound A, it is difficult to spread the small amount of molten alcohol compound A over the entire surface of the raw powder, making it difficult to produce a homogeneous composite powder. In addition, with this method, the molten alcohol compound A is likely to adhere to the wall of the mixing container, and the proportion that does not contribute to the compounding may increase, making it difficult to adjust the amount of alcohol compound A to be contained in the composite powder.
[0036] (Raw powder preparation process) The raw material powder may be any of those exemplified above.
[0037] (Preparation of alcohol solution A) The alcohol solution A includes an alcohol compound A and a solvent. The above-mentioned alcohol compound A can be used as the alcohol compound A. The concentration of the alcohol compound A in the alcohol solution is, for example, 0.01 to 2% by mass. The concentration of the alcohol compound A in the alcohol solution can be calculated from the content of the alcohol compound A in the composite powder and the amount of the alcohol solution A added in the manufacturing process. When it is necessary to lower the concentration of the alcohol solution A, a high-concentration alcohol solution A may be prepared first, and then the solution may be diluted with a solvent to lower the concentration. For example, a 1% by mass alcohol solution A may be prepared, and then a 0.1% by mass alcohol solution A may be prepared by mixing the 1% by mass alcohol solution A and the solvent in a mass ratio of 1:9.
[0038] The solvent is preferably a solvent that is relatively less harmful than a highly harmful solvent such as toluene. Examples of the solvent that is relatively less harmful include ethanol, isopropanol, and butyl acetate (hereinafter also referred to as "ethanol, etc."). The solvent may be used alone or in combination of two or more kinds.
[0039] The solubility of the alcohol compound A in the solvent is preferably 10% by mass or more, more preferably 15% by mass or more. In this case, the dissolution rate of the alcohol compound A in the solvent is high, and the alcohol solution A can be easily prepared. In this case, the occurrence of uneven mixing is sufficiently suppressed, and the raw material particles and the alcohol compound A can be easily mixed homogeneously. The solubility of the alcohol compound A in at least one solvent selected from the group consisting of ethanol, isopropanol, and butyl acetate is preferably 10% by mass or more (or 15% by mass or more).
[0040] The solubility referred to here is a value calculated by (M2 / (M1+M2))×100, where M2 (g) is the maximum mass of alcohol compound A that dissolves in a solvent of mass M1 (g) (temperature 25° C.).
[0041] If the additive has low solubility in the solvent, it takes a long time to prepare the additive solution, and the solvent evaporates when the additive solution and the raw powder are mixed, causing some of the additive to precipitate on the wall of the mixing tank, resulting in uneven mixing. If the additive is stearic acid, stearic acid has low solubility in ethanol, etc., so it takes a long time to prepare a stearic acid solution using ethanol, etc., and white solid substances are likely to adhere to the wall of the mixing tank when the stearic acid solution and the raw powder are mixed, resulting in uneven mixing.
[0042] (Mixing process of raw powder and alcohol solution A) This step is a step of wet-mixing the raw material powder with the alcohol compound A. That is, in the mixing step, an alcohol solution is added to the raw material powder while stirring the raw material powder, thereby obtaining a wet raw material powder.
[0043] The amount of alcohol compound A added is preferably 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of raw material powder. When the amount of alcohol compound A added is 0.1 parts by mass or less, the carbon content of the porous body is sufficiently reduced, and the strength of the molded body is sufficiently ensured, and the occurrence of cracks or partial defects in the sintered body due to a decrease in strength is sufficiently suppressed. When the amount of alcohol compound A added is 0.002 parts by mass or more, a composite powder with excellent weighing stability is easily obtained.
[0044] From the viewpoint of sufficiently suppressing the occurrence of uneven mixing and easily obtaining a homogeneous composite powder, the amount of alcohol solution A added is preferably 5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of raw material powder. When the amount of alcohol solution A added is within the above range, it is easy to adjust the entire raw material powder to a moderately wet state. When the amount of alcohol solution A added is small, it may be difficult for the alcohol compound A to spread uniformly throughout the entire raw material powder. When the amount of alcohol solution A added is large, the raw material powder becomes a slurry state, and a large amount of the alcohol solution A and raw material powder may adhere to the wall of the mixing container, and a large amount of the alcohol compound A may precipitate on the wall of the mixing container during drying (solvent removal process).
[0045] (Solvent removal process) In the solvent removal step, the wet raw material powder is dried while being stirred to remove the solvent, thereby obtaining a composite powder. The composite powder contains the raw material powder and the alcohol compound attached to the surface of the raw material powder particles. Drying can be performed by heating, reducing pressure, etc. When the solvent is ethanol, drying can be performed by heating at about 50 to 90°C.
[0046] When drying by heating, it is preferable to maintain the stirring state until the temperature of the raw material powder falls below the melting point of the alcohol compound A. If the stirring is stopped before the temperature of the raw material powder falls below the melting point of the alcohol compound A, the molten alcohol compound A may move, causing uneven mixing.
[0047] Here, Fig. 1 is a diagram showing an example of wet mixing of raw material powder and alcohol compound A. Raw material powder 100 is placed in a mixing container 110. A solution 200 of alcohol compound A is added to raw material powder 100 while stirring raw material powder 100. In this manner, raw material powder 100 in a wet state is obtained. After that, the raw material powder 100 in a wet state placed in the mixing container 110 is dried while being stirred to remove the solvent. In this manner, a composite powder is obtained.
[0048] [Method of manufacturing an anode body for electrolytic capacitor] The anode body for an electrolytic capacitor according to an embodiment of the present disclosure includes a step of preparing a composite powder, a step of molding the composite powder, a step of removing the alcohol compound A, a step of sintering the molded body, and a step of forming a dielectric layer.
[0049] (Preparation process of composite powder) In this step, the composite powder of the present disclosure is prepared. In this step, for example, the composite powder obtained by the above-mentioned manufacturing method is prepared.
[0050] (Composite powder molding process) In the molding step of the composite powder, the composite powder is filled into a predetermined molding die and pressure-molded to obtain a green body. This green body contains the alcohol compound A. In this step, a part of the anode wire may be embedded in the green body.
[0051] FIG. 2 is a diagram showing an example of a process for producing a compact from a composite powder. First, as shown in FIG. 2(a), the composite powder 300 is put into a weighing hole 420a having a certain volume formed by a weighing mold 420 and a lower mold 440, and the weighing hole 420a is filled with the composite powder 300 using a leveling slider 410. At this time, since the composite powder 300 containing the alcohol compound A has excellent weighing stability, the weighing can be stably performed by filling the weighing hole 420a with the powder 300 using the leveling slider 410. That is, the variation in the amount of powder filled into the weighing hole 420a can be reduced. This can reduce the mass variation of each of the molded body, the porous body, and the sintered body produced in the subsequent process.
[0052] 2(b), the weighed composite powder 300 is placed in a predetermined space 460 formed by a pressing die 430 and a lower die 440. After that, an upper die 450 is placed above the space 460, and the anode wire 6 is inserted into a predetermined hole of the upper die 450 so that a part of the anode wire 6 is placed in the space 460. 2(c), the pressing die 430 is moved in the direction of the arrow to pressure-mold the composite powder 300. In this manner, a compact 310 in which a part of the anode wire 6 is embedded is formed.
[0053] (Step of removing alcohol compound A) In the step of removing the alcohol compound A, the alcohol compound A contained in the molded body is removed. For example, the alcohol compound A contained in the molded body can be removed by vaporizing it. More specifically, the removal can be performed, for example, by heating the molded body to a predetermined temperature (a temperature equal to or higher than the boiling point of the alcohol compound A) under reduced pressure. When the boiling point of the alcohol compound A is 400°C or lower, the alcohol compound A can be removed at a temperature of about 400 to 500°C under reduced pressure. The reduced pressure in the removal step may be under vacuum, or may be under an atmosphere in which a small amount of inert gas such as Ar gas is introduced while evacuation is being performed using a vacuum pump.
[0054] In the case of the alcohol compound A, the weighing stability of the powder can be sufficiently increased by adding a small amount, so that the amount of the alcohol compound A remaining in the compact without being removed in the removal step can be sufficiently reduced. As a result, the carbon content derived from the alcohol compound A in the sintered compact obtained in the subsequent step can be sufficiently reduced.
[0055] (Sintering process of compact) In the sintering process of the molded body, the molded body from which the alcohol compound A has been removed is sintered to obtain a porous body (sintered body). Details of the porous body will be described later. The molded body can be sintered, for example, under reduced pressure at a temperature of 1200 to 1500°C. The reduced pressure in the sintering process is preferably under high vacuum.
[0056] Fig. 3 is a configuration diagram showing an example of equipment used in the step of removing the alcohol compound A and the step of sintering the compact. In Fig. 3, compact A is a compact containing the alcohol compound A, and compact B is a compact after the alcohol compound A removal treatment has been performed.
[0057] The equipment 500 includes a removal furnace 510 for removing the alcohol compound A from the compact A to obtain a compact B, a sintering furnace 520 for sintering the compact B, a recovery tank 530 for recovering the alcohol compound A removed from the compact A, a heat-retaining pipe 540, and a vacuum pump 550. The heat-retaining pipe 540 is disposed between the removal furnace 510 and the recovery tank 530.
[0058] The temperature inside the heat-insulating pipe 540 is adjusted to a temperature equal to or higher than the melting point of the alcohol compound A. This prevents the alcohol compound A from precipitating in the pipe 540. For example, when the melting point of the alcohol compound A is 100° C. or lower, the temperature inside the pipe 540 may be kept at about 120 to 150° C. In this case, there is no need to provide a pipe with a special heat-insulating structure, which is advantageous in terms of manufacturing costs.
[0059] Between the removal furnace 510 and the vacuum pump 550, the heat-retaining pipe 540 and the recovery tank 530 are arranged. The insides of the removal furnace 510, the heat-retaining pipe 540, and the recovery tank 530 are adjusted to a reduced pressure state by the vacuum pump 550. The sintering furnace 520 is also adjusted to a reduced pressure state by the vacuum pump 550. The recovery tank 530 is cooled with liquid nitrogen or the like, and the alcohol compound A is solidified and recovered. Valves may be provided between the removal furnace 510 and the sintering furnace 520, between the removal furnace 510 and the heat-retaining pipe 540, between the heat-retaining pipe 540 and the recovery tank 530, between the recovery tank 530 and the vacuum pump 550, and between the sintering furnace 520 and the vacuum pump 550. The valves may be opened and closed depending on the location and timing where reduced pressure is required.
[0060] The removing step and the sintering step using the apparatus of FIG. 3 will be described below. The compact A is supplied to a removal furnace 510 under reduced pressure, where the alcohol compound A is removed from the compact A, thereby producing a compact B. Next, the compact B is supplied to a sintering furnace 520 under reduced pressure, where it is sintered, thereby producing a sintered body. Meanwhile, the alcohol compound A removed by evaporation in the removal furnace 510 passes through a heat-insulating pipe 540 and is collected in a collection tank 530.
[0061] In FIG. 3, the removal furnace and the sintering furnace are provided separately, but a single furnace may be provided that functions as both a removal furnace and a sintering furnace. That is, the removal step and the sintering step may be performed in a single furnace. The removal furnace and / or the sintering furnace may be configured as a single furnace or as a plurality of furnaces. As for the vacuum pump, a vacuum pump connected to the collection tank and a vacuum pump connected to the sintering furnace may be provided separately.
[0062] (Dielectric layer forming process) In the dielectric layer forming step, a dielectric layer is formed on the surface of the porous body to obtain an anode body. The dielectric layer is formed, for example, by chemical conversion treatment. The details of the dielectric layer will be described later.
[0063] The electrolytic capacitor will be described in detail below.
[0064] [Electrolytic capacitor] The electrolytic capacitor includes a capacitor element. The capacitor element includes an anode body and a cathode portion. The anode body includes a porous body and a dielectric layer covering a surface of the porous body. The cathode portion is formed so as to cover the dielectric layer. The cathode portion includes at least a solid electrolyte layer.
[0065] The anode body may include a rod-shaped anode wire partly embedded in the porous body. When the porous body is a rectangular parallelepiped, the anode wire is planted from one end face of the rectangular parallelepiped. The anode wire may include a valve metal. A part of the anode wire is embedded in the porous body, and the remainder protrudes from the porous body. The remainder is connected to an anode lead terminal by welding or the like.
[0066] (Porous body) The porous body contains a valve metal, such as aluminum (Al), titanium (Ti), tantalum (Ta), niobium (Nb), zirconium (Zr), or hafnium (Hf).
[0067] The porous body is a sintered product of a compact of raw material particles (raw material powder) containing a valve metal. The particles may be particles of a valve metal, particles of an alloy containing a valve metal, or particles of a compound containing a valve metal. The particles may be of one type or a mixture of two or more types.
[0068] The porous body can be obtained by pressurizing raw material particles into a predetermined shape to obtain a molded body, and then sintering the molded body. For example, an anode wire may be placed at a predetermined position in a mold, raw material particles may be charged into the mold, and the molded body may be pressurized to obtain a molded body. The molded body may be sintered to obtain a porous body in which a part of the anode wire is embedded. The porous body is usually a rectangular parallelepiped.
[0069] (Dielectric layer) The dielectric layer is formed so as to cover the outer surface of the porous body and the inner wall surface of the pores of the porous body. The dielectric layer is formed, for example, by subjecting the porous body to a chemical conversion treatment and growing an oxide film on the surface of the porous body. The chemical conversion treatment may be performed by immersing the porous body in a chemical conversion solution to anodize the surface of the porous body. Alternatively, the surface of the porous body may be oxidized by heating the porous body in an atmosphere containing oxygen.
[0070] (Solid electrolyte layer) The solid electrolyte layer is disposed so as to cover at least a part of the dielectric layer. The solid electrolyte layer may be filled in the pores of the porous body via the dielectric layer and formed on the outer surface of the porous body. The solid electrolyte layer may be a laminate of two or more different solid electrolyte layers.
[0071] The solid electrolyte layer includes a conductive polymer. The conductive polymer may be a π-conjugated polymer, and examples of the conductive polymer include polypyrrole, polythiophene, polyaniline, and derivatives thereof. These may be used alone or in combination. The conductive polymer may be a copolymer of two or more monomers. The derivative of a conductive polymer means a polymer having a conductive polymer as a basic skeleton. For example, an example of a derivative of polythiophene includes poly(3,4-ethylenedioxythiophene) (PEDOT).
[0072] A dopant may be added to the conductive polymer. That is, the solid electrolyte layer may include a conductive polymer and a dopant. The conductive polymer may be included in the solid electrolyte layer in a state where the dopant is doped. The dopant may be selected according to the conductive polymer, and a known dopant may be used. Examples of the dopant include benzenesulfonic acid, alkylbenzenesulfonic acid, naphthalenesulfonic acid, alkylnaphthalenesulfonic acid, polystyrenesulfonic acid (PSS), and salts thereof. The solid electrolyte layer may include, for example, PEDOT doped with PSS.
[0073] The solid electrolyte layer containing a conductive polymer can be formed, for example, by impregnating a porous body (anode body) having a dielectric layer formed on its surface with a first treatment liquid containing a monomer (or oligomer), and then polymerizing the monomer (or oligomer) by electrolytic polymerization or chemical polymerization. In the case of chemical polymerization, the first treatment liquid contains, for example, a monomer (or oligomer), an oxidizing agent, and a solvent (or dispersion medium). Examples of the monomer include 3,4-ethylenedioxythiophene (EDOT) and pyrrole. The first treatment liquid may contain a dopant.
[0074] Alternatively, the solid electrolyte layer may be formed by impregnating a porous body (anode body) having a dielectric layer formed on its surface with a treatment liquid containing a conductive polymer, and drying the treatment liquid. The treatment liquid contains, for example, a conductive polymer, a solvent (or a dispersion medium), and, if necessary, a dopant.
[0075] (others) The capacitor element may include a cathode layer covering at least a portion of the solid electrolyte layer. The electrolytic capacitor may include an anode lead terminal and a cathode lead terminal electrically connected to the capacitor element, and an exterior resin arranged around the capacitor element. The cathode lead terminal is connected to the cathode part via a conductive member. The anode lead terminal is connected to an end of the anode wire protruding from the porous body. The shape, size, etc. of the capacitor element are not particularly limited, and may be a known capacitor element or a capacitor element having a similar configuration.
[0076] (cathode layer) The cathode layer may include a carbon layer formed on the solid electrolyte layer and a metal paste layer formed on the carbon layer. The carbon layer may be formed of a conductive carbon material such as graphite and a resin. The metal paste layer may be formed of metal particles (e.g., silver particles) and a resin, for example, a known silver paste.
[0077] (Conductive material) The cathode layer is connected to the connection portion of the cathode lead terminal by a conductive member. That is, the cathode layer (cathode portion) is electrically connected to the cathode lead terminal. The conductive member is made of a material having electrical conductivity. The conductive member may be formed using a material containing metal particles (e.g., silver particles) and a resin, and may be formed using, for example, a known metal paste (e.g., silver paste). The conductive member is formed by heating the metal paste. The conductive member may be made of a plurality of conductive layers of different types.
[0078] (Exterior resin) The exterior resin is disposed around the capacitor element so that the capacitor element is not exposed on the surface of the electrolytic capacitor. Furthermore, the exterior resin insulates the anode lead terminal and the cathode lead terminal. The exterior resin may be a known exterior resin used for electrolytic capacitors. For example, the exterior resin may be formed using an insulating resin material used for sealing the capacitor element. The exterior resin may be formed by placing the capacitor element in a mold, and introducing an uncured thermosetting resin and a filler into the mold by a transfer molding method, a compression molding method, or the like, and curing the resin.
[0079] Examples of the exterior resin include epoxy resin, phenolic resin, silicone resin, melamine resin, urea resin, alkyd resin, polyurethane, polyimide, unsaturated polyester, etc. The exterior resin may contain substances other than resin (such as inorganic filler).
[0080] (Cathode lead terminal) A part of the cathode lead terminal is exposed from the exterior resin and used as a cathode external terminal. The material of the cathode lead terminal may be any material that can be used as a material of a cathode lead terminal of an electrolytic capacitor. For example, a known material of a cathode lead terminal used in an electrolytic capacitor may be used. The cathode lead terminal may be formed by processing a metal sheet (including a metal plate and a metal foil) made of a metal (copper, copper alloy, etc.) by a known metal processing method.
[0081] (Anode lead terminal) A part of the anode lead terminal is exposed from the exterior resin and used as an anode external terminal. The material of the anode lead terminal may be any material that can be used as a material of an anode lead terminal of an electrolytic capacitor. For example, a known material of an anode lead terminal used in an electrolytic capacitor may be used. The anode lead terminal may be formed by processing a metal sheet (including a metal plate and a metal foil) made of a metal (copper, copper alloy, etc.) by a known metal processing method.
[0082] 4 is a cross-sectional view showing a schematic example of the electrolytic capacitor according to the present embodiment, but the electrolytic capacitor according to the present embodiment is not limited to this.
[0083] Electrolytic capacitor 20 includes capacitor element 10, exterior resin 11 that seals capacitor element 10, and anode lead terminal 12 and cathode lead terminal 13 that are electrically connected to capacitor element 10. Anode lead terminal 12 and cathode lead terminal 13 are each partially exposed from exterior resin 11. Anode lead terminal 12 and cathode lead terminal 13 are partially covered by exterior resin 11 together with capacitor element 10.
[0084] Capacitor element 10 includes an anode body 1, a solid electrolyte layer 2 formed on the anode body 1, and a cathode layer 3 formed on the solid electrolyte layer 2. Anode body 1 includes a porous body 4 containing a valve metal, and a dielectric layer 5 covering the porous body 4. Dielectric layer 5 is formed so as to cover the outer surface of porous body 4 and the inner wall surfaces of the pores.
[0085] The porous body 4 has a substantially rectangular parallelepiped shape and has six side surfaces. A part of the anode wire 6 extends from one side surface of the porous body 4. That is, the anode wire 6 has a first portion 6a embedded in the porous body 4 from one side surface of the porous body 4, and a second portion 6b extending from the one side surface of the porous body 4. The second portion 6b is joined to an anode lead terminal 12 by welding or the like.
[0086] The solid electrolyte layer 2 is formed so as to cover at least a portion of the dielectric layer 5. The solid electrolyte layer 2 fills the pores of the porous body 4 (anode body 1). The solid electrolyte layer 2 is formed so as to cover the outer surface S of the porous body 4 and the inner wall surfaces of the pores via the dielectric layer 5.
[0087] The cathode layer 3 is formed so as to cover the surface of the solid electrolyte layer 2. The cathode layer 3 has a carbon layer 3a formed so as to cover the solid electrolyte layer 2, and a metal paste layer 3b formed on the surface of the carbon layer 3a. The cathode lead terminal 13 is joined to the cathode layer 3 (metal paste layer 3b) via a conductive member 8. The carbon layer 3a contains a conductive carbon material such as graphite and a resin. The metal paste layer 3b contains, for example, metal particles (e.g., silver) and a resin. The configuration of the cathode layer 3 is not limited to this configuration. The cathode layer 3 may have any configuration as long as it has a current collecting function.
[0088] Additional Notes The above description of the embodiments discloses the following techniques. (Technology 1) A composite powder used for producing a porous body included in an anode body of an electrolytic capacitor, The composite powder includes a raw material powder including a valve action metal and an alcohol compound (excluding a polymer) attached to a surface of a particle of the raw material powder, The melting point of the alcohol compound is 35°C or higher. (Technology 2) The composite powder according to claim 1, wherein the melting point of the alcohol compound is 35°C or more and 120°C or less. (Technology 3) 3. The composite powder according to claim 1 or 2, wherein the boiling point of the alcohol compound is 400° C. or lower. (Technology 4) The composite powder according to any one of Techniques 1 to 3, wherein the alcohol compound includes at least one selected from the group consisting of monohydric alcohol compounds and dihydric alcohol compounds. (Technology 5) The composite powder according to the present invention, wherein the monohydric alcohol compound is at least one selected from the group consisting of 1-tetradecanol, 1-pentadecanol, 1-hexadecanol, 1-heptadecanol, 1-octadecanol, 1-nonadecanol, 1-icosanol, 1-docosanol, 1-tetracosanol, 1-hexacosanol, 1-octacosanol, and 1-triacontanol. (Technology 6) The dihydric alcohol compound is at least one selected from the group consisting of 1,2-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 2,3-dimethyl-2,3-butanediol, 2,2-diethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,9-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,2-hexadecanediol, and 1,16-hexadecanediol. The composite powder according to technique 4. (Technology 7) 7. The composite powder according to any one of Techniques 1 to 6, wherein the content of the alcohol compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder. (Technology 8) 8. The composite powder according to any one of techniques 1 to 7, wherein the solubility of the alcohol compound in at least one solvent selected from the group consisting of ethanol, isopropanol, and butyl acetate is 10% by mass or more. (Technology 9) The composite powder according to any one of techniques 1 to 8, wherein the anode body includes the porous body containing the valve metal, and a dielectric layer covering a surface of the porous body. (Technology 10) A method for producing a composite powder used for producing a porous body included in an anode body of an electrolytic capacitor, comprising the steps of: preparing a raw material powder including a valve metal; A step of preparing an alcohol solution containing an alcohol compound (excluding a polymer) having a melting point of 35° C. or higher and a solvent; adding the alcohol solution to the raw material powder while stirring the raw material powder to obtain the raw material powder in a wet state; and drying the wet raw material powder while stirring to remove the solvent, thereby obtaining a composite powder. The composite powder comprises the raw material powder and the alcohol compound adhered to surfaces of particles of the raw material powder. (Technology 11) The melting point of the alcohol compound is 35°C or more and 120°C or less. (Technology 12) 12. The method for producing a composite powder according to claim 10 or 11, wherein the boiling point of the alcohol compound is 400° C. or lower. (Technology 13) 13. The method for producing a composite powder according to any one of Techniques 10 to 12, wherein the alcohol compound includes at least one selected from the group consisting of monohydric alcohol compounds and dihydric alcohol compounds. (Technology 14) The method for producing a composite powder according to the present invention, wherein the monohydric alcohol compound includes at least one selected from the group consisting of 1-tetradecanol, 1-pentadecanol, 1-hexadecanol, 1-heptadecanol, 1-octadecanol, 1-nonadecanol, 1-icosanol, 1-docosanol, 1-tetracosanol, 1-hexacosanol, 1-octacosanol, and 1-triacontanol. (Technology 15) The method for producing a composite powder according to the present invention, wherein the dihydric alcohol compound is at least one selected from the group consisting of 1,2-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 2,3-dimethyl-2,3-butanediol, 2,2-diethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,9-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,2-hexadecanediol, and 1,16-hexadecanediol. (Technology 16) The method for producing a composite powder according to any one of Techniques 10 to 15, wherein the content of the alcohol compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder. (Technology 17) 17. The method for producing a composite powder according to any one of Techniques 10 to 16, wherein the amount of the alcohol solution added is 5 mass % or more and 20 mass % or less per 100 mass parts of the raw material powder. (Technology 18) 18. The method for producing a composite powder according to any one of Techniques 10 to 17, wherein the solvent includes at least one selected from the group consisting of ethanol, isopropanol, and butyl acetate. (Technology 19) 19. The method for producing a composite powder according to any one of claims 10 to 18, wherein the anode body includes the porous body containing the valve metal, and a dielectric layer covering a surface of the porous body. (Technology 20) A step of preparing a composite powder including a raw material powder containing a valve metal and an alcohol compound (excluding a polymer) attached to a surface of a particle of the raw material powder; A step of filling the composite powder into a predetermined molding die and compressing the composite powder to obtain a molded body; removing the alcohol compound contained in the molded body; sintering the molded body from which the alcohol compound has been removed to obtain a porous body; forming a dielectric layer on the surface of the porous body to obtain an anode body; Including, The method for producing an anode body for an electrolytic capacitor, wherein the alcohol compound has a melting point of 35° C. or higher. (Technology 21) 21. The method for producing an anode body for an electrolytic capacitor according to claim 20, wherein the melting point of the alcohol compound is 35° C. or higher and 120° C. or lower. (Technology 22) 22. The method for producing an anode body for an electrolytic capacitor according to claim 20 or 21, wherein the alcohol compound has a boiling point of 400° C. or lower. (Technology 23) 23. The method for producing an anode body for an electrolytic capacitor according to any one of claims 20 to 22, wherein the alcohol compound includes at least one selected from the group consisting of monohydric alcohol compounds and dihydric alcohol compounds. (Technology 24) The method for producing an anode for an electrolytic capacitor according to Technical 23, wherein the monohydric alcohol compound includes at least one selected from the group consisting of 1-tetradecanol, 1-pentadecanol, 1-hexadecanol, 1-heptadecanol, 1-octadecanol, 1-nonadecanol, 1-icosanol, 1-docosanol, 1-tetracosanol, 1-hexacosanol, 1-octacosanol, and 1-triacontanol. (Technology 25) The method for producing an anode body for an electrolytic capacitor according to Technology 23 or 24, wherein the dihydric alcohol compound includes at least one selected from the group consisting of 1,2-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 2,3-dimethyl-2,3-butanediol, 2,2-diethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,9-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,2-hexadecanediol, and 1,16-hexadecanediol. (Technology 26) The method for producing an anode body for an electrolytic capacitor according to any one of Techniques 20 to 25, wherein the content of the alcohol compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder.
[0089] [Example] Hereinafter, the present disclosure will be specifically described based on examples and comparative examples, but the present disclosure is not limited to the following examples.
[0090] Examples 1 to 13 (Preparation of composite powder) Ta powder (average particle size: 80 μm, CV value: 70 kCV) was prepared as the raw material powder. An alcohol solution containing alcohol compound A (additive) and ethanol (solvent) was prepared as the additive solution. As the alcohol compound A, 1,10-decanediol (melting point 70° C. or higher), 2,5-dimethyl-2,5-hexanediol (melting point 80° C. or higher), or 1-hexadecanol (melting point 40° C. or higher) was used. All of these have a boiling point of 400° C. or lower and a solubility in ethanol of 10 mass % or higher.
[0091] The alcohol solution was added to the raw powder while stirring it to obtain a wet raw powder (Figure 1). The amount of the alcohol compound added was the value (parts by mass) shown in Table 1 per 100 parts by mass of the raw powder. The concentration of the alcohol solution was appropriately adjusted so that the amount of the alcohol solution added was within the range of 5 to 20 parts by mass per 100 parts by mass of the raw powder. The wet raw material powder was heated and dried at a temperature of 90° C. or less while stirring to remove the solvent. In this manner, a composite powder (Ta particles having an alcohol compound adhered to their surfaces: composite particles) containing the raw material powder and the alcohol compound adhered to the surfaces of the raw material powder particles was obtained.
[0092] (Preparation of Molded Body) A specified amount of composite powder was filled into a specified molding die by leveling and weighing (Fig. 2(a)). One end of an anode wire was embedded in the part filled with composite powder (Fig. 2(b)). The composite powder was then pressure molded to obtain a compact (Fig. 2(c)). The outer shape of the compact was a rectangular parallelepiped (0.8 mm x 3.7 mm x 5.2 mm). Ta wire was used as the anode wire.
[0093] (Preparation of sintered body) The alcohol compounds contained in the compact were removed under reduced pressure at 400 to 500°C. Next, the green body from which the alcohol compound had been removed was sintered under reduced pressure at 1300 to 1400° C. At this time, the sintering temperature and sintering time were adjusted so that the shrinkage rate was about 10%. In this manner, a porous body (Ta sintered body) in which a part of the anode wire was embedded was obtained.
[0094] Comparative Example 1 An acrylic resin solution (solvent: toluene) was prepared as an additive solution instead of an alcohol solution. The amount of acrylic resin added was 1.5 parts by mass per 100 parts by mass of raw material powder. A composite powder was produced, a molded body was produced, and a sintered body was produced in the same manner as in Example 1 except for the above.
[0095] Comparative Example 2 Instead of the alcohol solution, a camphor solution (solvent: methanol) was prepared as an additive solution. The amount of camphor added was 1.5 parts by mass per 100 parts by mass of raw material powder. Other than the above, a composite powder was prepared in the same manner as in Example 1, a compact was prepared, and a sintered body was prepared.
[0096] Comparative Example 3 No additive was used. That is, a green body was produced in the same manner as in Example 1 except that a raw material powder was used instead of a composite powder, and then a sintered body was produced.
[0097] The green bodies and sintered bodies produced in the above examples and comparative examples were evaluated as follows.
[0098] [evaluation] (Rate of non-defective molded products) 300 molded bodies were produced using an automatic molding machine, and the masses of the 300 molded bodies were measured. The percentage of the number of molded bodies whose masses were within ±0.5% of the target mass (non-defective products) among the 300 molded bodies was calculated as the yield rate of the molded bodies. When the weighing stability of the powder is high, the mass variation of the molded bodies is reduced, and the yield rate of the molded products is increased.
[0099] (Rate of cracks (chips) in molded bodies) One hundred pieces were randomly selected from the molded bodies produced above. The percentage of the number of molded bodies that had cracks (chips) among the 100 molded bodies was calculated as the crack (chip) occurrence rate (%).
[0100] (Carbon content of sintered body) The carbon content (ppm by mass) of the sintered body was determined using about 1 g of the sintered body using a carbon / sulfur analyzer (manufactured by Horiba, Ltd.).
[0101] (LC in liquid) The sintered body with a part of the anode wire embedded therein was subjected to chemical conversion treatment (anodization). The chemical conversion treatment was performed in a 0.02 mass% phosphoric acid aqueous solution at a chemical conversion voltage of 80 V and a temperature of 60°C. A specified voltage of less than 80 V was applied to the sintered body (anode body) after the chemical conversion treatment in the phosphoric acid aqueous solution, and the current value at the time when a specified time had elapsed since the start of the voltage application was obtained as the in-liquid LC (leakage current).
[0102] (Coefficient of variation indicating the variation in the amount of powder filled into the weighing hole) The coefficient of variation, which indicates the variation in the amount of powder filled into the weighing hole, was determined for the composite powders of Examples 4, 9, 11, and 13. The coefficient of variation was similarly determined for the raw material powder in Comparative Example 3. The weighing stability was evaluated based on the coefficient of variation.
[0103] The weighing stability was evaluated using an evaluation jig set shown in Fig. 5. The evaluation jig set 600 in Fig. 5 includes a filling jig 610, a weighing jig 620, and a metal plate 640, and was configured to assume filling of the composite powder 300 into the weighing hole 420a using the leveling slider 410 in Fig. 2(a).
[0104] Specifically, a hollow cylindrical filling jig 610 (inner diameter 20 mm) made of stainless steel, a plate-shaped weighing jig 620 (thickness 4 mm) made of stainless steel having a weighing hole 620a (diameter 3 mm) with a circular cross section in the center, and a metal plate 640 were prepared. As shown in FIG. 5, the weighing jig 620 was placed on the metal plate 640, and the filling jig 610 was placed on the weighing jig 620. 2 g of powder 700 was poured into the hollow portion 610a of the filling jig 610, and the filling jig 610 was reciprocated three times (in the direction of the arrow shown in FIG. 5) so as to pass through the weighing hole 620a of the weighing jig 620. In this way, the powder 700 was filled into the weighing hole 620a. Next, the powder 700 filled into the weighing hole 620a was taken out and its mass was measured. Such measurements were repeated 10 times. The standard deviation and average value of the 10 measured values were calculated. The coefficient of variation (%) indicating the variation in the amount of powder 700 filled into weighing hole 620a was calculated by (standard deviation / average value)×100.
[0105] The evaluation results are shown in Table 1. The amounts of additives added in Table 1 are shown per 100 parts by mass of the raw material powder.
[0106] [Table 1]
[0107] In Examples 1 to 12, good weighing stability was obtained for the composite powder, the carbon content of the sintered body was reduced, and LC in the liquid was reduced. When the amount of the alcohol compound added was 0.1 parts by mass or less, no cracks (chipping) were observed in the molded body (Examples 1 to 7, 9 to 12). When the amount of the alcohol compound added was 0.002 parts by mass or more, the weighing stability was further improved (Examples 2 to 12). In Example 13, the coefficient of variation was small, confirming the improvement of the weighing stability.
[0108] When the additive was an acrylic resin, it was necessary to add a large amount to ensure weighing stability, which resulted in a high carbon content and an increase in LC in the liquid (Comparative Example 1). When camphor was added to Ta powder with an average particle size of less than 100 μm to produce a composite powder, the weighing stability decreased and the defective rate of the molded body increased (Comparative Example 2). When the raw material powder (Ta powder) was used as is instead of the composite powder, the weighing stability decreased and the defective rate of the molded body increased (Comparative Example 3).
[0109] The composite powders of Examples 4, 9, 11 and 13 had smaller coefficients of variation, which indicate the variation in the amount of powder filled into the weighing hole, and improved weighing stability, compared to the raw powder of Comparative Example 3. [Industrial Applicability]
[0110] The composite powder according to the present disclosure is suitable for use in producing a porous body contained in an anode body of an electrolytic capacitor. [Explanation of symbols]
[0111] 1: anode body, 2: solid electrolyte layer, 3: cathode layer, 3a: carbon layer, 3b: metal paste layer, 4: porous body, 5: dielectric layer, 6: anode wire, 6a: first part, 6b: second part, 8: conductive member, 10: capacitor element, 11: exterior resin, 12: anode lead terminal, 13: cathode lead terminal, 20: electrolytic capacitor, 100: raw material powder, 110: mixing vessel, 200: solution of alcohol compound A, 300: composite powder, 310: compound Shape, 410: leveling slider, 420: weighing mold, 430: press mold, 440: lower mold, 450: upper mold, 460: space, 500: equipment, 510: alcohol compound A removal furnace, 520: sintering furnace, 530: alcohol compound A recovery tank, 540: heat retention piping, 550: vacuum pump, 600: evaluation jig set, 610: filling jig, 610a: hollow portion, 620: weighing jig, 620a: weighing hole, 640: metal plate, 700: powder
Claims
1. A composite powder used for manufacturing a porous body included in an anode body of an electrolytic capacitor, The composite powder includes a raw material powder including a valve metal and an alcohol compound (excluding a polymer) attached to a surface of a particle of the raw material powder, The melting point of the alcohol compound is 35°C or higher.
2. The composite powder according to claim 1 , wherein the melting point of the alcohol compound is 35° C. or more and 120° C. or less.
3. The composite powder according to claim 1 , wherein the boiling point of the alcohol compound is 400° C. or lower.
4. The composite powder according to claim 1 , wherein the alcohol compound includes at least one selected from the group consisting of monohydric alcohol compounds and dihydric alcohol compounds.
5. The composite powder according to claim 4, wherein the monohydric alcohol compound includes at least one selected from the group consisting of 1-tetradecanol, 1-pentadecanol, 1-hexadecanol, 1-heptadecanol, 1-octadecanol, 1-nonadecanol, 1-icosanol, 1-docosanol, 1-tetracosanol, 1-hexacosanol, 1-octacosanol, and 1-triacontanol.
6. The dihydric alcohol compound is 1,2-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 2,3-dimethyl-2,3-butanediol, 2,2-diethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,9-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,2-hexadecanediol, and 1,16-hexadecanediol. The composite powder according to claim 4, which includes at least one selected from the group consisting of hexadecanediol.
7. The composite powder according to claim 1 , wherein a content of the alcohol compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder.
8. The composite powder according to claim 1 , wherein the alcohol compound has a solubility of 10% by mass or more in at least one solvent selected from the group consisting of ethanol, isopropanol, and butyl acetate.
9. The composite powder according to claim 1 , wherein the anode body comprises the porous body containing the valve metal, and a dielectric layer covering a surface of the porous body.
10. A method for producing a composite powder used for producing a porous body included in an anode body of an electrolytic capacitor, comprising the steps of: preparing a raw material powder including a valve metal; A step of preparing an alcohol solution containing an alcohol compound (excluding a polymer) having a melting point of 35° C. or higher and a solvent; adding the alcohol solution to the raw material powder while stirring the raw material powder to obtain the raw material powder in a wet state; and drying the wet raw material powder while stirring to remove the solvent, thereby obtaining a composite powder. The composite powder comprises the raw material powder and the alcohol compound adhered to surfaces of particles of the raw material powder.
11. The method for producing a composite powder according to claim 10, wherein the melting point of the alcohol compound is 35°C or higher and 120°C or lower.
12. The method for producing a composite powder according to claim 10, wherein the alcohol compound has a boiling point of 400°C or lower.
13. The method for producing a composite powder according to claim 10, wherein the alcohol compound includes at least one selected from the group consisting of monohydric alcohol compounds and dihydric alcohol compounds.
14. The method for producing a composite powder according to claim 13, wherein the monohydric alcohol compound includes at least one selected from the group consisting of 1-tetradecanol, 1-pentadecanol, 1-hexadecanol, 1-heptadecanol, 1-octadecanol, 1-nonadecanol, 1-icosanol, 1-docosanol, 1-tetracosanol, 1-hexacosanol, 1-octacosanol, and 1-triacontanol.
15. The dihydric alcohol compound is 1,2-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 2,3-dimethyl-2,3-butanediol, 2,2-diethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,9-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,2-hexadecanediol, and 1,16-hexadecanediol. The method for producing a composite powder according to claim 13, comprising at least one selected from the group consisting of:
16. The method for producing a composite powder according to claim 10, wherein a content of the alcohol compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder.
17. The method for producing a composite powder according to claim 10, wherein the amount of the alcohol solution added is 5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the raw material powder.
18. The method for producing a composite powder according to claim 10, wherein the solvent includes at least one selected from the group consisting of ethanol, isopropanol, and butyl acetate.
19. The method for producing a composite powder according to claim 10 , wherein the anode body comprises the porous body containing the valve metal, and a dielectric layer covering a surface of the porous body.
20. A step of preparing a composite powder including a raw material powder containing a valve action metal and an alcohol compound (excluding a polymer) attached to a surface of a particle of the raw material powder; A step of filling the composite powder into a predetermined molding die and compressing the composite powder to obtain a molded body; removing the alcohol compound contained in the molded body; sintering the molded body from which the alcohol compound has been removed to obtain a porous body; forming a dielectric layer on the surface of the porous body to obtain an anode body; Including, The method for producing an anode body for an electrolytic capacitor, wherein the alcohol compound has a melting point of 35° C. or higher.
21. 21. The method for producing an anode body for an electrolytic capacitor according to claim 20, wherein the alcohol compound has a melting point of 35°C or higher and 120°C or lower.
22. 21. The method for producing an anode body for an electrolytic capacitor according to claim 20, wherein the alcohol compound has a boiling point of 400° C. or lower.
23. 21. The method for producing an anode body for an electrolytic capacitor according to claim 20, wherein the alcohol compound includes at least one selected from the group consisting of monohydric alcohol compounds and dihydric alcohol compounds.
24. The method for producing an anode body for an electrolytic capacitor according to claim 23, wherein the monohydric alcohol compound includes at least one selected from the group consisting of 1-tetradecanol, 1-pentadecanol, 1-hexadecanol, 1-heptadecanol, 1-octadecanol, 1-nonadecanol, 1-icosanol, 1-docosanol, 1-tetracosanol, 1-hexacosanol, 1-octacosanol, and 1-triacontanol.
25. The dihydric alcohol compound is at least one selected from the group consisting of 1,2-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 2,3-dimethyl-2,3-butanediol, 2,2-diethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,9-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,2-hexadecanediol, and 1,16-hexadecanediol. The method for producing an anode body for an electrolytic capacitor according to claim 23.
26. 21. The method for producing an anode body for an electrolytic capacitor according to claim 20, wherein a content of the alcohol compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder.
Citation Information
Patent Citations
Method for producing powder metallurgical compact without binder contamination and compact produced by the method
JP2003509583A
Tantalum powder, anode and capacitor containing the same, and methods for producing the same
JP2020500260A
solid electrolytic capacitor
JP2022533161A